Cardiac Surgery in Jehovah's Witness Patients: Experience of a Brazilian Tertiary Hospital - Valle,Felipe Homem (2017)
Abstract Introduction: The outcomes of Jehovah's Witness (JW) patients submitted to open heart surgery may vary across countries and communities. The aim of this study was to describe the morbidity and mortality of JW patients undergoing cardiac surgery in a tertiary hospital center in Southern Brazil. Methods: A case-control study was conducted including all JW patients submitted to cardiac surgery from 2008 to 2016. Three consecutive surgical non-JW controls were matched to each selected JW patient. The preoperative risk of death was estimated through the mean EuroSCORE II. Results: We studied 16 JW patients with a mean age of 60.6±12.1 years. The non-JW group included 48 patients with a mean age of 63.3±11.1 years (P=0.416). Isolated coronary artery bypass graft surgery was the most frequent surgery performed in both groups. Median EuroSCORE II was 1.29 (IQR: 0.66-3.08) and 1.43 (IQR: 0.72-2.63), respectively (P=0.988). The mortality tended to be higher in JW patients (18.8% vs. 4.2%, P=0.095), and there was a higher difference between the predicted and observed mortality in JW patients compared with controls (4.1 and 18.8% vs. 2.1 and 4.2%). More JW patients needed hemodialysis in the postoperative period (20.0 vs. 2.1%, P=0.039). Conclusion: We showed a high rate of in-hospital mortality in JW patients submitted to cardiac surgery. The EuroSCORE II may underestimate the surgical risk in these patients.